The Diagnosis of Mild Haemophilia by the Partial Thromboplastin Time Test. WFH/ICTH Study of the Manchester Method - O'Brien, P F; North, W R S; Ingram, G I C (Thrombosis and Haemostasis, 1981)
In two trials, various methods of performing the partial thromboplastin time test (PTT) were compared with the method described from Manchester by Poller and Thomson (1) and Poller et al. (2), for their ability to diagnose mild haemophilia. In the first trial, 64 laboratories in various countries compared their own methods and reagents with the Manchester method on three coded haemophilic plasmas distributed freeze-dried and on four local fresh normals collected in each laboratory. In the second trial, seven well-standardized commercial methods were tested in pairs against the Manchester method in seven experienced laboratories on 22 mild haemophilic samples and six normal samples each coded and distributed frozen. PTTs were related to factor VIII: C level.In the first trial, the better standardized methods gave more consistent results than others; but even so there were large differences between laboratories even on normal plasmas. The second trial established a reasonably linear relationship between log PTT and log VIII :C in the range 15-150 iu/dl; but different methods did not greatly vary in their ability to detect a mild haemophilic defect; this was confirmed by calculating the index Slope/(Residual S. D.) which was used to provide a rank order. Scatter diagrams suggested that a proportion of mild haemophilic samples would be likely to have PTTs within the normal range by any method. It is concluded that the Manchester method does not detect mild haemophilia with greater discrimination than the other methods studied; that each laboratory must establish its own normal range even if using a well-standardized method; and that in screening patients a PTT must be supplemented by a discriminating history.
Keywords: Manchester partial thromboplastin time method; Mild haemophilia; Diagnosis